SOCIAL COMMUNICATION AND THEOLOGY – COMMUNICATION THEOLOGY - Eilers, Franz-Josef (Asian Horizons, 2012)
This presentation has two major parts. At first we look at documents and approaches to theology in a more general way which is followed by a more detailed overview on the proposed field of Communication Theology.